Field theory in time dependent background: Superradiance and Sonoluminescence - Karmakar, Rajesh (My University, 2024)
The dissipative nature of time dependent systems is well known to have an intriguing feature of superradiance like phenomena when interacting with radiation either classically or quantum mechanically. In this thesis we have considered two particular dynamical systems arising in two different realms namely, oscillating black holes (BH) in the sky and oscillating bubbles in the laboratory. In the first part of the thesis, we studied the classical scattering of massless fields from oscillating BHs and calculated the absorption cross-section. In the second part of the thesis, we have considered a laboratory system of an oscillating gas bubble, where we have proposed a framework and studied the phenomena of quantum mechanical particle production mapping the system into an analog geometric background.
Maity, Debaprasad